Croatia's rush to join the EU: Hasty admission would damage the country, other candidate countries and the EU - Andrea Despot; Dušan Reljić (Stiftung Wissenschaft und Politik (SWP), 2011)
If the government and the opposition in Zagreb were to have their way, in the next few weeks the remaining stumbling blocks to Croatian EU accession would be removed, and by the end of June 2011 accession negotiations in progress since 2005 would be concluded. Yet, in certain key areas - primarily in respect of the rule of law - the acquis communautaire is still not being fully implemented. The European Commission and EU member states should therefore resist wishes for an expedited process. They must insist that deficits are first remedied
Keywords: 320